Podcast or Perish : Peer Review and Knowledge Creation for the 21th Century - Beckstead, Lori; Cook, Ian M.; McGregor, Hannah; Spinelli, Martin; Dann, Lance (New York : Bloomsbury Academic, 2024)
"A call to action for the scholarly community - introducing the merger of podcasting and peer review to encourage academics to think about the medium as an alternative outlet for research output"--
Includes index
Bibliography: pages 191-210
Keywords: Podcasting; Communication in education -- Technological innovations